Alfabetização em tempos de BNCC: o que dizem professores e professoras alfabetizadoras? - Sigolo, Sthefany (2023)
The implementation process of Base Nacional Comum Curricular (BNCC) brought conceptual and structural changes to the literacy's cycle, reflecting on the teacher's concepts and practices. This research carried out an investigation into what literacy teachers say about literacy in BNCC, and aimed to analyse how literacy teachers understand, conceive and practice literacy, considering the implementation of the Base and the institutional contexts, curriculum policies and practical experiences that permeate it. The investigation was supported by the theoretical contributions of Soares (2006, 2009, 2021 a, b, c, d) and Mortatti (2010, 2013) on literacy, and of Gimeno Sacristán (2013, 2017) and Young (2007, 2014) about the curriculum. Therefore, a qualitative research was developed, whose data were collected from a documental analysis of the Base regarding literacy in the two first years of Elementary School, as well as the conduction of semi-structured interviews with literacy teachers who worked with literacies classes in the past five years in a peripheral public school in the city of São Carlos, São Paulo. In the results, regarding literacy, was observed a conceptual backward's movement of BNCC and, from the statements of the interviewees, stands out the little significant participation of the literacy teachers in the curriculum reformulation process, the self-reinterpretation that the teachers give to the curriculum in their literacys pratices, and the need of continuing education, institutional support and collective planning.